ANALISIS SEMIOTIKA FILM ANIMASI TANPA BATAS PADA PESAN KEKERASAN BERBASIS GENDER - -Pohan, Syafruddin; Khairani, Dewi Suci; Sinulingga, Yohana; Pulungan, Tuty Alawiyah (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
Abstract The stigmatization of women with disabilities as weak and helpless is one of the reasons why women with disabilities are vulnerable to sexual violence. One of them is depicted in the animated film entitled Tanpa Batas which was uploaded on the YouTube channel called Tanpa Batas in June 2023 and is also the object of research. This research aims to understand the message conveyed in the animation and help Indonesian society increase awareness regarding sexual violence. This research uses a critical paradigm with a qualitative approach and John Fiske's semiotic analysis based on appearance codes, costumes, expressions, body language and text. The results of this research are shown in several scenes of sexual violence that occurred depicted in visual form, namely photographs.